2017
DOI: 10.1053/j.semperi.2016.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and growth factors in the developing intestine and during necrotizing enterocolitis

Abstract: Cytokines and growth factors play diverse roles in the uninflamed fetal/neonatal intestinal mucosa and in the development of inflammatory bowel injury during necrotizing enterocolitis (NEC). During gestational development and the early neonatal period, the fetal/premature intestine is exposed to high levels of many “inflammatory” cytokines and growth factors, first via swallowed amniotic fluid in utero and then, after birth, in colostrum and mother’s milk. This article reviews the dual, seemingly counter-intui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 102 publications
1
42
0
2
Order By: Relevance
“…In this regard, several groups have shown that amniotic fluid administration can limit NEC 38,5362 , which Hackam et al showed to be due to effects on inhibition of the degree of TLR4 signaling 38 . It is noteworthy that as the intestinal mucosa of the developing fetus is bathed in swallowed amniotic fluid and TLR4 activation is restricted, the fetus is protected from unexpected activation of TLR4 by ascending bacteria in utero, which could otherwise lead to intestinal injury and premature birth.…”
Section: Curtailing Bacterial Signaling In the Premature Intestine Tomentioning
confidence: 99%
“…In this regard, several groups have shown that amniotic fluid administration can limit NEC 38,5362 , which Hackam et al showed to be due to effects on inhibition of the degree of TLR4 signaling 38 . It is noteworthy that as the intestinal mucosa of the developing fetus is bathed in swallowed amniotic fluid and TLR4 activation is restricted, the fetus is protected from unexpected activation of TLR4 by ascending bacteria in utero, which could otherwise lead to intestinal injury and premature birth.…”
Section: Curtailing Bacterial Signaling In the Premature Intestine Tomentioning
confidence: 99%
“…TNF‐α and IL‐6 are proinflammatory cytokines that play a critical role in normal host resistance to infection, serving as immmunomodulators of inflammatory responses (Nyachoti et al., ). Both are primarily created by activated macrophages through many signals, such as ionophores, lipopolysaccharide, and antigenic stimulation by pathogenic microorganisms (MohanKumar et al., ). TNF‐α and IL‐6 are mostly derived from lymphocytes and macrophages, but it was produced at a lower concentration with pre‐probiotics; perhaps this type of cytokines is also produced by endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a pro-inflammatory state in preterm infants has been associated with decreased IGF-1 levels [24]. It has also been demonstrated that colostrum and maternal milk contain high concentrations of anti-inflammatory cytokines [25].…”
Section: The Route Of Nutrient Administrationmentioning
confidence: 99%